Współczesne czasopisma kulturalno-literackie na Warmii i Mazurach = Contemporary cultural and literary magazinesin Warmia and Mazury - Romulewicz, Anita (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The region of Warmia and Mazury can?t boast about a spectacular number of periodicals on artistic and literary topics, however, those that existed on the press market played a significant role in creating the image of today's culture of the region. Titles such as "Borussia" or "Portret" created around themselves, in their time, a network of mutual dependencies, built recognizable spaces, and took an undeniably important voice in local and broader discussions. Nowadays, in Warmia and Mazury, one can notice a new model of journalism related to culture, art and literature, clearly less concentrated, where experience meets with a fresh look, artistic "I" dominates over "us", where changes occur in the areas of publisher-author, author-reader, reader-media. The last two decades have been the time of "opening". One of the co-creators of new trends in the cultural life of Olsztyn and the region is the Regional Public Library in Olsztyn, from 2008 the publisher of the magazine "VariArt" (in printed and electronic versions).
Keywords: czasopisma kulturalno-literackie; czasopisma artystyczne; Warmia i Mazury; kultura regionalna; cultural and literary magazines; art magazines; Warmia and Mazury; regional culture